ZMY Management Services / Nurul Shahira Nisa Ismail - Ismail, Nurul Shahira Nisa (Universiti Teknologi MARA, Perlis, Faculty of Business and Management, 2021)
This report summarizing my experience throughout internship training in ZMY Management Services for five months and a half. For over 20 years of operating, ZMY Management Services able to offer a wide range of services throughout the country. This company offers services in corporate companies’ secretaries, corporation & personal income tax, accounting services, incorporation of the company. There are many advantages I gain in completing my industrial training at the company. Other than that, I can learn and understand the company's business and services as well experiencing real-life working situations. During my six months internship, I was able to prepare the SWOT analysis of the company. The strengths, weaknesses, opportunities, and threats. By inspecting using SWOT analysis, the company can take advantage of their strength and opportunities and improving their weakness and threats. Moreover, the company can take the initiatives to encounter their competition to achieve chances for success. It is important to identify a company’s competitive advantage to decide on services and products that the company produces better than competitors. The company can identify the internal and external advantages and the problem of the company to compete with other firms. Especially, due to pandemic situations, the company has been affected more in terms of productivity and operation of the company.